Organization and implementation of physical education in various medical groups (survey of the problem) - Боднар [Bodnar І.] Іванна (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Construction management of physical education in schools is possible only on condition that the existing problems and clarify aspects insufficiently studied. Purpose – to set the state of problems of organization and implementation of physical education students of various medical groups. Analyzed over 50 abstracts of dissertations and over 200 scientific articles on physical education in special medical groups conducted mal conversations with teachers and physical education teacher observations over the organization of physical education in schools. One of the possible ways to improve the organizational methods of physical education can be to develop the concept and organization of the content of inclusive physical education of pupils of special medical groups, and the justification of technology implementation. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>